Sentenced for Failure to Provide Family Assistance increases overcrowding in Chiclayo Prison - Rojas Ruiz, Segundo Adán (2023)
The general objective of the study was to describe the situation that causes the admission of those convicted of that criminal offense considering the housing capacity of the Chiclayo prison. It is a basic type of research, non-experimental design, with a qualitative approach. The population and sample was made up of 48 inmates, the technique was the document analysis and the instrument the Data Collection Sheet. It is concluded that overcrowding is critical due to the excessive entry of defendants for various crimes, including omission of family assistance, the consequences of which are: (i) deficient therapeutic service that affects the Resocialization process; (ii) increased security risk, due to inappropriate behavior of the inmates; (iii) violation of the dignity of the inmate due to lack of privacy, poor personal hygiene and restriction of basic services. It is recommended that the Judiciary apply the provision of community services; to the Judiciary and the Public Ministry, consider alternatives to effective imprisonment for petty crimes; to the National Penitentiary Institute, expand the Chiclayo prison with rooms for bedrooms, workshops for work and classrooms for study.